2013
DOI: 10.1002/oby.20197
|View full text |Cite
|
Sign up to set email alerts
|

Late pregnancy reversal from excessive gestational weight gain lowers risk of childhood overweight-A cohort study

Abstract: Objective: Whether reversal to adequate gestational weight gain (GWG) in the third trimester reverses the risk for childhood overweight associated with excessive GWG is assessed. Design and Methods: In a retrospective cohort study in 6,665 mother-child pairs, pre-pregnancy weight and the temporal course of GWG were collected from medical records. Overweight as defined by International Obesity Task Force was assessed at a mean age of 5.8 years. Main exposures were exceeding week-specific cut-off values for GWG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
1
8
1
1
Order By: Relevance
“…The present analysis differs in two ways from previous studies published by our group [ 17 , 20 ]. 1) Here, we used continuous instead of dichotomized explanatory (kg/week instead of excessive weight gain) and outcome (BMI z-score and waist circumference instead of overweight) variables.…”
Section: Discussioncontrasting
confidence: 68%
“…The present analysis differs in two ways from previous studies published by our group [ 17 , 20 ]. 1) Here, we used continuous instead of dichotomized explanatory (kg/week instead of excessive weight gain) and outcome (BMI z-score and waist circumference instead of overweight) variables.…”
Section: Discussioncontrasting
confidence: 68%
“…However, the reporting of weight occurred shortly after the patient was weighed at a pre‐natal visit or delivery, perhaps reducing the likelihood of major bias. Like previous reports , we did not find evidence that the effect of total GWG on childhood obesity varied by pre‐pregnancy BMI, or that the effect of early excessive GWG was modified by late GWG, but our sample size may have been too small to detect these effects.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, we found that the increased risk of childhood obesity was statistically significant only among women who gained excessively in both early and late pregnancy. Unlike our study, von Kries and colleagues used data from a large Bavarian retrospective cohort and found that regardless of GWG at <14 weeks or 14 to <26 weeks, GWG ≥26 weeks may contribute to the risk of childhood obesity .…”
Section: Discussionmentioning
confidence: 61%
“…This is true even when first and second trimester weight gain have exceeded the recommended guidelines. 12 …”
Section: Maternal Body Mass Fetal Weight Gain and Infant Birthweightmentioning
confidence: 99%